The Efficacy and Safety of FSK0808, Filgrastim Biosimilar: A Multicenter, Non-randomized Study in Japanese Patients with Breast Cancer - Sagara, Y.; Sato, K.; Fukuma, E.; Higaki, K.; Mizutani, M.; Osaki, A.; Takano, T.; Tokuda, Y.; Ohno, S.; Masuda, N.; Suzuki, M.; Saeki, T. (Japanese journal of clinical oncology, 2013)
FSK0808 is a filgrastim biosimilar. This study assessed the efficacy and safety of FSK0808 in patients with breast cancer. One hundred and four breast cancer patients undergoing chemotherapy were enrolled in the study. FSK0808 was used to treat the neutropenia experienced by the patients in the course of their chemotherapy. Efficacy was evaluated by the recovery of absolute neutrophil count following FSK0808 administration based on the duration of neutropenia in patients who received pre- or postoperative chemotherapy containing fluorouracil, epirubicin and cyclophosphamide. Adverse events were evaluated in accordance with the Common Terminology Criteria for Adverse Events version 3.0. The incidence of febrile neutropenia and generation of an anti-granulocyte colony-stimulating factor antibody were also evaluated. The average duration of neutropenia in Cycle 2 was 2.2 days with a standard deviation of 1.5 days. The upper limit of the 97.5% one-sided confidence interval was 2.5 days and was confirmed not to exceed 3.0 days, which was defined as the threshold value of absolute neutrophil count recovery. The incidence of febrile neutropenia across all treatment cycles was 34.6%. Observed adverse drug reactions with an incidence of > 5% were back pain (60.6%), bone pain (9.6%), alanine aminotransferase increase (8.7%), aspartate aminotransferase increase (5.8%) and arthralgia (5.8%). Production of the anti-granulocyte colony-stimulating factor antibody was not observed in any patient during the study. FSK0808 was safe and well tolerated in breast cancer patients undergoing chemotherapy and effectively stimulated neutrophil recovery.